2018
DOI: 10.3389/fendo.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neuroendocrine Stress Response-Related Circulating MicroRNAs as Biomarkers for Type 2 Diabetes Mellitus and Insulin Resistance

Abstract: BackgroundChronic stress plays an important role in the development of type 2 diabetes mellitus (T2DM) and insulin resistance (IR). MicroRNAs (miRNAs) play key roles in mediating stress responses by regulating the expression of target genes. This study systematically screened and identified the neuroendocrine stress response-related circulating miRNAs which are associated with T2DM and IR.MethodsBased on the differential plasma expression profiles between individuals with and without T2DM, stress-related miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 38 publications
1
37
1
Order By: Relevance
“…Increasing evidence suggests that miRNAs play a significant role in the diagnosis of T2DM or as therapeutic targets 48 50 and may also regulate endothelial cell function and angiogenesis 51 , 52 . In this study, we found significant differences in the serum miRNA expression profiles of Han Chinese T2DM patients with or without CLI.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that miRNAs play a significant role in the diagnosis of T2DM or as therapeutic targets 48 50 and may also regulate endothelial cell function and angiogenesis 51 , 52 . In this study, we found significant differences in the serum miRNA expression profiles of Han Chinese T2DM patients with or without CLI.…”
Section: Discussionmentioning
confidence: 99%
“…A vitamin D-induced increase in miR-152 levels correlated negatively with HbA1c, while a decrease in miR-192 levels correlated positively with fasting glucose in individuals at risk for T2D [63]. In a Chinese cohort with IFG, upregulated levels of miR-144, miR-20a, and let-7b increased the risk for T2D and positively correlated with HOMA-IR, while decreased levels of miR-142 increased the risk for IFG and negatively correlated with HOMA-IR [70].…”
Section: Mirnas As Biomarkers For Pre-diabetes (Pre-dm) and T2dmentioning
confidence: 90%
“…Besides, transmission electron microscopy showed that exosome had a diameter of ~100 nm ( Figure 1B ), which was in accordance with the reported size. Based on previous studies which profiled circulating microRNAs of type 1 and 2 diabetes [ 13 , 14 ], we focused on the most dysregulated miR-144-3p. Similarly, compared with the circulating exosome from normal mice (NGexo), qPCR (n=3 each group) confirmed miR-144-3p was upregulated in diabetic exosomes (DMexo; Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%